Redescription of Panonychus caglei Mellott, 1968, with ontogenetic development (Acari: Tetranychidae) - Negm, Mohamed W.; Gotoh, Tetsuo (Zootaxa, 2021)
A redescription of the adult stages of Panonychus caglei Mellott, 1968 (Acari: Tetranychidae), is presented based on new material collected from Japan, and type specimens (holotype and paratypes). Morphological differences in the setation of legs have been reported and measurements of taxonomic characters are added. We also have described the ontogenetic development of the juvenile stages. The ventral idiosomal chaetotaxy in larval stage lacks pregenital and genital setae which are added consecutively through development. The pregenital pair of setae appears in the protonymphs while the first pair of genital setae is firstly observed in the deutonymphal stage.